Pelatihan dan Pendampingan UMKM dalam Penentuan Harga Pokok Penjualan dengan Metode Full Costing - Anggun Puspita Rini; Tutut Dewi Astuti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
The determination of the Cost of Goods Sold (COGS) is a crucial element for micro, small, and medium enterprises (MSMEs), especially in setting competitive prices and achieving the desired profits. However, many MSMEs still face challenges in understanding and applying the appropriate COGS determination methods. This training aims to enhance the capacity of MSMEs in calculating COGS using the Full Costing method through training and mentoring programs. The methodology used includes delivering material, calculation simulations, and evaluating the application of the Full Costing method. The research results indicate an improvement in participants' understanding of cost components as well as their ability to calculate COGS in a more structured and accurate manner. This program has made a positive contribution to the financial management of MSMEs and is expected to serve as a model for capacity development for small business owners in the future.